Organic silicon pouring sealant with high thermal conductivity and low viscosity and preparation method thereof

By introducing titanate coupling agent and modified graphite powder into the silicone potting glue, the formulation and process are optimized, and the problem of difficulty in achieving low viscosity and high thermal conductivity at the same time is solved, and efficient heat dissipation and excellent mechanical properties are achieved.

CN119552629APending Publication Date: 2025-03-04ANHUI SMART NEW MATERIALS CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411859813.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Traditional silicone potting glues are difficult to achieve low viscosity and high thermal conductivity at the same time, and cannot meet the needs of high-performance electronic equipment for efficient heat dissipation.

Method used

By introducing titanate coupling agent and modified graphite powder into the raw materials, the formulation and preparation process of the sealant are optimized, including pretreatment, mixing, additive additives, vacuum defoaming, addition of catalysts and curing agents, and curing processes, forming a silicone potting glue with high thermal conductivity and low viscosity.

Benefits of technology

It realizes that the sealant has high thermal conductivity while maintaining low viscosity, improves the heat dissipation ability of electronic components, and enhances the mechanical strength, flexibility and temperature resistance of the sealant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552629A_ABST
    Figure CN119552629A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic silicon pouring sealants, and discloses a high-thermal-conductivity low-viscosity organic silicon pouring sealant and a preparation method thereof, and the sealant comprises the following raw materials by weight: 80-90 parts of alpha, omega-dihydroxy polydiethylsiloxane; 4 to 8 parts of polyphenyl siloxane; 100 to 120 parts of spherical aluminum nitride; 3 to 7 parts of epoxy butyl oleate; 0.8 to 1.2 parts of organic bentonite; 0.5 to 0.9 part of a titanate coupling agent; 0.8 to 0.9 part of dibutyltin dibutyrate; 0.15 to 0.20 part of dibutyltin oxide; 0.08 to 0.15 part of phosphotriester; the titanate coupling agent, the tris (2, 3-dibromopropyl) phosphate and the graphite powder are introduced into the raw materials, the graphite powder is subjected to surface modification treatment in the pretreatment stage, and the modified graphite powder is more firmly combined with a sealing compound matrix, so that the sealing compound can still keep stable performance at an extreme temperature; by integrating the respective characteristics of the raw materials, the sealing compound finished product disclosed by the invention has the advantage of high heat-conducting property while having low viscosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organosilicon potting adhesives, and in particular to a high-thermal-conductivity and low-viscosity organosilicon potting adhesive and a preparation method thereof. Background Art

[0002] In the prior art, silicone potting glue is widely used in the bonding, sealing, potting and coating protection of electronic components. This material is known for its excellent weather resistance and high and low temperature resistance. It can be used for a long time in the temperature range of -60℃ to 200℃. At the same time, it has a low curing shrinkage rate, no damage to components, and excellent insulation performance. However, as electronic components tend to be miniaturized and dense, higher requirements are placed on the thermal conductivity of potting materials. Although traditional silicone potting glue has a certain thermal conductivity, it is difficult to meet the needs of high-performance electronic equipment for efficient heat dissipation. Although increasing the filling amount of thermal conductive filler can improve the thermal conductivity, it will lead to an increase in the viscosity of the potting glue and poor fluidity, which is not conducive to potting operations in practical applications. Therefore, the development of a silicone potting glue that can maintain low viscosity for processing and application, while having high thermal conductivity, has become a hot spot and difficulty in current research. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of the deficiencies in the prior art, the present invention provides a high thermal conductivity and low viscosity silicone potting adhesive and a preparation method thereof, which has the advantages of achieving both low viscosity and high thermal conductivity, and solves the problem that traditional silicone potting adhesives cannot achieve both low viscosity and high thermal conductivity.

[0005] (II) Technical solution

[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a high thermal conductivity and low viscosity organic silicone potting glue, wherein the raw materials of the potting glue and their weight proportions are: 80-90 parts of α,ω-dihydroxypolydiethylsiloxane; 4-8 parts of polyphenylsiloxane; 100-120 parts of spherical aluminum nitride; 3-7 parts of epoxy butyl oleate; 0.8-1.2 parts of organic bentonite; 0.5-0.9 parts of titanate coupling agent; 0.8-0.9 parts of dibutyltin dibutyrate; 0.15-0.20 parts of dibutyltin oxide; 0.08-0.15 parts of triester phosphate; and 1.4-1.9 parts of graphite powder.

[0007] Preferably, the raw materials of the sealant and their weight parts are: 90 parts of α,ω-dihydroxypolydiethylsiloxane; 4 parts of polyphenylsiloxane; 105 parts of spherical aluminum nitride; 7 parts of epoxy butyl oleate; 0.95 parts of organic bentonite; 0.7 parts of titanate coupling agent; 0.81 parts of dibutyltin dibutyrate; 0.16 parts of dibutyltin oxide; 0.09 parts of triester phosphate; and 1.7 parts of graphite powder.

[0008] Preferably, the raw materials of the sealant and their weight parts are: 85 parts of α,ω-dihydroxypolydiethylsiloxane; 5 parts of polyphenylsiloxane; 100 parts of spherical aluminum nitride; 4 parts of epoxy butyl oleate; 0.89 parts of organic bentonite; 0.58 parts of titanate coupling agent; 0.87 parts of dibutyltin dibutyrate; 0.18 parts of dibutyltin oxide; 0.095 parts of triester phosphate; and 1.88 parts of graphite powder.

[0009] Preferably, the α,ω-dihydroxypolydiethylsiloxane and polyphenylsiloxane constitute the base polymer material; the spherical aluminum nitride and graphite powder constitute the filler; the epoxy butyl oleate is a plasticizer, and the organic bentonite is both a plasticizer and a modifier; the titanate coupling agent is a coupling agent; the dibutyltin dibutyrate, dibutyltin oxide and triester phosphate are catalysts and curing agents.

[0010] Preferably, a method for preparing a high thermal conductivity and low viscosity organic silicone potting adhesive is prepared according to the weight range of the raw materials of the above-mentioned high thermal conductivity and low viscosity organic silicone potting adhesive, and comprises the following preparation steps:

[0011] Step 1, raw material preparation: weigh α, ω-dihydroxy polydiethylsiloxane, polyphenylsiloxane, spherical aluminum nitride, graphite powder, epoxy butyl oleate, organic bentonite, titanate coupling agent, dibutyltin dibutyrate, dibutyltin oxide and triester phosphate according to the formula weight;

[0012] Step 2, pretreatment: surface modification of filler-graphite powder by chemical treatment method;

[0013] Step 3, mixing: using a high shear mixer to mix α,ω-dihydroxypolydiethylsiloxane, polyphenylsiloxane, spherical aluminum nitride and graphite powder under set conditions to form a mixture;

[0014] Step 4: Adding additives: lower the mixer temperature to 30-35°C, add epoxy butyl oleate, organic bentonite and titanate coupling agent to the mixture, and mix well;

[0015] Step 5, vacuum degassing: vacuum degassing the mixture in the mixer;

[0016] Step 6: Adding catalyst and curing agent: After lowering the temperature of the mixer and setting the mixing time, add dibutyltin dibutyrate, dibutyltin oxide and triester phosphate into the mixture and mix well;

[0017] Step 7: Curing process: transfer the mixture to a potting container and set the required temperature and time for curing to form the final silicone potting glue;

[0018] Step 8: Post-processing: After the curing, the sealant is cut, polished and cleaned according to the manufacturer's needs;

[0019] Step 9: Performance testing: Conduct performance tests on thermal conductivity, mechanical strength, flexibility and temperature resistance of the finished sealant.

[0020] Preferably, in step 2, the filler-graphite powder is subjected to a modification treatment process:

[0021] S1.1, pretreatment: put the graphite material into the oven, set the oven temperature to 90℃-110℃, and the oven drying time is 2-4h. When the moisture content of the material is detected to be lower than 0.1% by mass, stop the oven;

[0022] S1.2, graphite powder: the dried material is powdered, the powdering time is set between 6-12 minutes, the powdering speed is set to 20000-25000r / min, and the graphite powder particles are controlled between 50-100 microns;

[0023] S1.3, strong acid treatment method: immerse the graphite powder in 30% concentrated sulfuric acid and react at 80-95°C for 5-7 minutes to make the surface of the graphite particles hydrophilic.

[0024] Preferably, the mixing conditions in step three are: setting the temperature to 30-35° C., setting the stirring speed to 300-400 rpm, and setting the mixing time to 30-35 min.

[0025] Preferably, the vacuum degassing conditions in step 5 are: the vacuum degree is set to 0.05-0.1 MPa, and the degassing time is between 10-15 min.

[0026] Preferably, the conditions for adding the catalyst and curing agent in step six are as follows: lowering the mixer temperature to 20-25° C. and setting the mixing time to 20-30 min.

[0027] Preferably, the curing process in step seven is: transferring the mixture to a potting container, controlling the temperature between 140-150° C., controlling the time between 8-10 h, maintaining the potting pressure between 2-3 N, and performing vacuum treatment at the same time, and curing under this condition to form a final silicone potting glue product.

[0028] Compared with the prior art, the present invention provides a high thermal conductivity and low viscosity organic silicone potting adhesive and a preparation method thereof, which has the following beneficial effects:

[0029] 1. The present invention introduces a titanate coupling agent into the raw materials, which helps to improve the thermal conductivity of the sealant and optimize its viscosity, so that the sealant can effectively conduct heat while maintaining good fluidity, and the addition of tris(2,3-dibromopropyl) phosphate helps to enhance the flame retardant properties of the sealant. The graphite powder is surface-modified in the pretreatment stage, which not only improves the mechanical strength and flexibility of the sealant, but also enhances the temperature resistance and thermal conductivity of the sealant. The modified graphite powder is more firmly bonded to the sealant matrix, so that the sealant can still maintain stable performance at extreme temperatures. Combining the above raw material characteristics, the sealant finished product of the present invention can have low viscosity and high thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A flow chart was prepared for the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] See also Figure 1 , a high thermal conductivity and low viscosity silicone potting glue, the raw materials of the potting glue and their weight ranges are: 80-90 parts of α, ω-dihydroxy polydiethylsiloxane; 4-8 parts of polyphenylsiloxane; 100-120 parts of spherical aluminum nitride; 3-7 parts of epoxy butyl oleate; 0.8-1.2 parts of organic bentonite; 0.5-0.9 parts of titanate coupling agent; 0.8-0.9 parts of dibutyltin dibutyrate; 0.15-0.20 parts of dibutyltin oxide; 0.08-0.15 parts of tri(2,3-dibromopropyl) phosphate; 1.4-1.9 parts of graphite powder.

[0033] Specifically, α,ω-dihydroxypolydiethylsiloxane and polyphenylsiloxane constitute the basic polymer material; the spherical aluminum nitride and graphite powder constitute the filler; the epoxy butyl oleate is a plasticizer, the organic bentonite is both a plasticizer and a modifier; the titanate coupling agent is a coupling agent; the dibutyltin dibutyrate, dibutyltin oxide and triester phosphate are catalysts and curing agents.

[0034] Specifically, a method for preparing a high thermal conductivity and low viscosity organic silicone potting adhesive is prepared according to the weight range of the raw materials of the above-mentioned high thermal conductivity and low viscosity organic silicone potting adhesive, and includes the following preparation steps:

[0035] Step 1, raw material preparation: weigh α, ω-dihydroxy polydiethylsiloxane, polyphenylsiloxane, spherical aluminum nitride, graphite powder, epoxy butyl oleate, organic bentonite, titanate coupling agent, dibutyltin dibutyrate, dibutyltin oxide and tris(2,3-dibromopropyl) phosphate according to the formula weight (when preparing these raw materials, it must be ensured that they are not contaminated and meet the requirements of product specifications);

[0036] Step 2, pretreatment: surface modification of filler-graphite powder by chemical treatment method; (the purpose is to make the filler and the matrix better combined, thereby improving the overall thermal conductivity, improving its dispersibility in silicone oil and reducing viscosity);

[0037] Step 3, mixing: using a high shear mixer to mix α,ω-dihydroxy polydiethylsiloxane, polyphenylsiloxane, spherical aluminum nitride and graphite powder under set conditions to form a mixture (adjusting the stirring speed can avoid filler agglomeration to ensure the uniformity of the mixture, and the mixing time can ensure sufficient dispersion, which is crucial to the performance of the final product);

[0038] Step 4, adding additives: lower the mixer temperature to 30-35°C, add epoxy butyl oleate, organic bentonite and titanate coupling agent to the mixture, and mix evenly (plasticizers and modifiers can improve the flexibility, processability and rheological properties of the product, while coupling agents are used to improve the interface bonding between the filler and the matrix, further enhancing the performance of the product);

[0039] Step 5, vacuum degassing: vacuum degassing the mixture in the mixer; (vacuum degassing the mixture can effectively remove bubbles in the system, which is very important for improving the stability and performance of the final product. The presence of bubbles may cause defects in the product during the curing process, thereby affecting its performance);

[0040] Step 6, adding catalyst and curing agent: after lowering the temperature of the mixer and setting the mixing time, add dibutyltin dibutyrate, dibutyltin oxide and triester phosphate into the mixture and mix evenly (the catalyst and curing agent can ensure the smooth progress of the reaction and the stability of the final product, and this step helps to increase the curing performance of the product);

[0041] Step 7, curing process: transfer the mixture to a potting container and set the required temperature and time for curing to form the final silicone potting compound (this step requires strict control of temperature and time to ensure that the product can be fully cured and achieve the expected performance);

[0042] Step 8. Post-processing: The cured sealant is cut, polished and cleaned according to the manufacturer's needs (to meet specific application requirements, this step helps to improve the product's appearance quality and performance);

[0043] Step 9. Performance testing: Conduct performance tests on the thermal conductivity, mechanical strength, flexibility and temperature resistance of the finished sealing compound (to ensure that the product meets the predetermined performance standards, including thermal conductivity, mechanical strength, flexibility and temperature resistance, and is put into production after passing the tests. Through these tests, it can be evaluated whether the product performance meets the design requirements and the product can be optimized).

[0044] Specifically, in step 2, the filler-graphite powder is subjected to modification treatment:

[0045] S1.1, pretreatment: put the graphite material into the oven, set the oven temperature to 90℃-110℃, and the oven drying time is 2-4h. When the moisture content of the material is detected to be lower than 0.1% by mass, stop the oven;

[0046] S1.2, graphite powder: the dried material is powdered, the powdering time is set between 6-12 minutes, the powdering speed is set to 20000-25000r / min, and the graphite powder particles are controlled between 50-100 microns;

[0047] S1.3, strong acid treatment method: immerse the graphite powder in 30% concentrated sulfuric acid and react at 80-95°C for 5-7 minutes to make the surface of the graphite particles hydrophilic.

[0048] Specifically, the mixing conditions in step three are: setting the temperature to 30-35° C., setting the stirring speed to 300-400 rpm, and setting the mixing time to 30-35 min.

[0049] Specifically, the vacuum degassing conditions in step 5 are: the vacuum degree is set to 0.05-0.1 MPa, and the degassing time is between 10-15 minutes.

[0050] Specifically, the conditions for adding the catalyst and curing agent in step 6 are as follows: lower the mixer temperature to 20-25° C. and set the mixing time to 20-30 min.

[0051] Specifically, the curing process in step seven is: transfer the mixture to a potting container, control the temperature between 140-150°C, control the time between 8-10h, maintain the potting pressure between 2-3N, and perform vacuum treatment at the same time, and cure under this condition to form the final silicone potting glue product.

[0052] Example 1

[0053] The raw materials of the sealant and their weight parts are: 80-90 parts of α,ω-dihydroxypolydiethylsiloxane; 4-8 parts of polyphenylsiloxane; 100-120 parts of spherical aluminum nitride; 3-7 parts of epoxy butyl oleate; 0.8-1.2 parts of organic bentonite; 0.5-0.9 parts of titanate coupling agent; 0.8-0.9 parts of dibutyltin dibutyrate; 0.15-0.20 parts of dibutyltin oxide; 0.08-0.15 parts of tri(2,3-dibromopropyl) phosphate; and 1.4-1.9 parts of graphite powder.

[0054] Example 2

[0055] The raw materials of the sealant and their weight parts are: 90 parts of α,ω-dihydroxypolydiethylsiloxane; 4 parts of polyphenylsiloxane; 105 parts of spherical aluminum nitride; 7 parts of epoxy butyl oleate; 0.95 parts of organic bentonite; 0.7 parts of titanate coupling agent; 0.81 parts of dibutyltin dibutyrate; 0.16 parts of dibutyltin oxide; 0.09 parts of triester phosphate; and 1.7 parts of graphite powder (modified).

[0056] Example 3

[0057] The raw materials of the sealant and their weight parts are: 85 parts of α,ω-dihydroxypolydiethylsiloxane; 5 parts of polyphenylsiloxane; 100 parts of spherical aluminum nitride; 4 parts of epoxy butyl oleate; 0.89 parts of organic bentonite; 0.58 parts of titanate coupling agent; 0.87 parts of dibutyltin dibutyrate; 0.18 parts of dibutyltin oxide; 0.095 parts of triester phosphate; and 1.88 parts of graphite powder.

[0058] Comparative Example 1

[0059] The raw materials of the sealant and their weight parts are: 80-90 parts of α,ω-dihydroxypolydiethylsiloxane; 4-8 parts of polyphenylsiloxane; 100-120 parts of spherical aluminum nitride; 3-7 parts of epoxy butyl oleate; 0.8-1.2 parts of organic bentonite; 0.8-0.9 parts of dibutyltin dibutyrate; 0.15-0.20 parts of dibutyltin oxide; 0.08-0.15 parts of tri(2,3-dibromopropyl) phosphate; 1.4-1.9 parts of graphite powder (0.5-0.9 parts of titanate coupling agent are deleted on the basis of Example 1).

[0060] Comparative Example 2

[0061] The raw materials of the sealant and their weight parts are: 90 parts of α, ω-dihydroxypolydiethylsiloxane; 4 parts of polyphenylsiloxane; 105 parts of spherical aluminum nitride; 7 parts of epoxy butyl oleate; 0.95 parts of organic bentonite; 0.7 parts of titanate coupling agent; 0.81 parts of dibutyltin dibutyrate; 0.16 parts of dibutyltin oxide; 0.09 parts of triester phosphate; 1.7 parts of graphite powder (ordinary grinding) (based on Example 2, the filler-graphite powder is not modified, but the number of parts remains unchanged).

[0062] Comparative Example 3

[0063] The raw materials of the sealant and their weight parts are: 85 parts of α, ω-dihydroxypolydiethylsiloxane; 5 parts of polyphenylsiloxane; 100 parts of spherical aluminum nitride; 4 parts of epoxy butyl oleate; 0.89 parts of organic bentonite; 0.58 parts of titanate coupling agent; 0.87 parts of dibutyltin dibutyrate; 0.28 parts of dibutyltin oxide; 1.88 parts of graphite powder (based on Example 3, 0.095 parts of triester phosphate were deleted and 0.1 parts of dibutyltin oxide were added).

[0064] The examples and comparative examples were made into sealing glue according to the preparation steps of the present invention, and the finished products were tested for viscosity, thermal conductivity, mechanical strength, flexibility and temperature resistance. The test data are shown in the following table:

[0065]

[0066] Note: Viscosity test: Use a rotational viscometer to measure the viscosity of the sample at 25°C; Thermal conductivity test: Use the laser flash method to measure the thermal conductivity of the sample at room temperature; Mechanical strength test: Measure the tensile strength of the sample through a tensile test; Flexibility test: Measure the flexibility of the sample through a 180-degree bending test; Temperature resistance test: Measure the performance retention of the sample at high temperatures through a thermal stability test.

[0067] The following is an analysis of the test results of the finished product sealing performance of the embodiment and the comparative example:

[0068] Viscosity (Pa·s): The viscosities of Examples 1, 2 and 3 are 0.8, 0.75 and 0.78 Pa·s, respectively, while the viscosities of Comparative Examples 1, 2 and 3 are 0.9, 0.76 and 0.82 Pa·s, respectively. The viscosities of the Examples are all lower than those of the Comparative Examples. When a titanate coupling agent is added, the viscosity of the sealant is slightly reduced, indicating that adding a titanate coupling agent to the raw materials is helpful to improve the fluidity and construction performance of the sealant.

[0069] Thermal conductivity (W / m·K): The thermal conductivity of Examples 1, 2 and 3 are 1.2, 1.3 and 1.25 W / m·K, respectively, while the thermal conductivity of Comparative Examples 1, 2 and 3 are 1.1, 1.15 and 1.2 W / m·K, respectively. The thermal conductivity of the embodiments is higher than that of the comparative examples, indicating that the addition of titanate coupling agent and the surface modification of graphite powder can improve the thermal conductivity of the sealant.

[0070] Mechanical strength (MPa): The mechanical strengths of Examples 1, 2 and 3 are 25, 27 and 26 MPa, respectively, while the mechanical strengths of Comparative Examples 1, 2 and 3 are 24, 26 and 25 MPa, respectively. The mechanical strengths of the embodiments are all higher than or equal to the comparative examples, indicating that the titanate coupling agent and modified graphite powder are helpful to improve the mechanical strength of the sealant.

[0071] Flexibility (mm): The flexibility of Examples 1, 2 and 3 is 5, 5.5 and 5.2 mm, respectively, while the flexibility of Comparative Examples 1, 2 and 3 is 4.8, 5 and 5.1 mm, respectively. The flexibility of the Examples is higher than that of the Comparative Examples, indicating that the modified graphite powder helps to improve the flexibility of the sealant.

[0072] Temperature resistance (℃): The temperature resistance of Examples 1, 2 and 3 are 200, 210 and 205℃, respectively, while the temperature resistance of Comparative Examples 1, 2 and 3 are 190, 205 and 198℃, respectively. The temperature resistance of the embodiments is higher than that of the comparative examples, indicating that the addition of titanate coupling agent and modified graphite powder helps to improve the temperature resistance of the sealant.

[0073] Therefore, based on the above analysis, the embodiment performs better than the comparative example in terms of viscosity, thermal conductivity, mechanical strength, flexibility and temperature resistance, indicating that the addition of titanate coupling agent and modified graphite powder can improve the comprehensive performance of the sealant.

[0074] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high thermal conductivity and low viscosity silicone potting adhesive, characterized in that: The raw materials of the sealant and their weight ranges are: 80-90 parts of α,ω-dihydroxypolydiethylsiloxane; 4-8 parts of polyphenylsiloxane; 100-120 parts of spherical aluminum nitride; 3-7 parts of epoxy butyl oleate; 0.8-1.2 parts of organic bentonite; 0.5-0.9 parts of titanate coupling agent; 0.8-0.9 parts of dibutyltin dibutyrate; 0.15-0.20 parts of dibutyltin oxide; 0.08-0.15 parts of triester phosphate; and 1.4-1.9 parts of graphite powder.

2. The high thermal conductivity and low viscosity organic silicone potting adhesive according to claim 1, characterized in that: The raw materials of the sealant and their weight parts are: 90 parts of α,ω-dihydroxypolydiethylsiloxane; 4 parts of polyphenylsiloxane; 105 parts of spherical aluminum nitride; 7 parts of epoxy butyl oleate; 0.95 parts of organic bentonite; 0.7 parts of titanate coupling agent; 0.81 parts of dibutyltin dibutyrate; 0.16 parts of dibutyltin oxide; 0.09 parts of triester phosphate; and 1.7 parts of graphite powder.

3. The high thermal conductivity and low viscosity organic silicone potting adhesive according to claim 1, characterized in that: The raw materials of the sealant and their weight parts are: 85 parts of α,ω-dihydroxypolydiethylsiloxane; 5 parts of polyphenylsiloxane; 100 parts of spherical aluminum nitride; 4 parts of epoxy butyl oleate; 0.89 parts of organic bentonite; 0.58 parts of titanate coupling agent; 0.87 parts of dibutyltin dibutyrate; 0.18 parts of dibutyltin oxide; 0.095 parts of triester phosphate; and 1.88 parts of graphite powder.

4. The high thermal conductivity and low viscosity organic silicone potting adhesive according to claim 1, characterized in that: The α,ω-dihydroxy polydiethylsiloxane and polyphenylsiloxane constitute a basic polymer material; the spherical aluminum nitride and graphite powder constitute a filler; the epoxy butyl oleate is a plasticizer, the organic bentonite is both a plasticizer and a modifier; the titanate coupling agent is a coupling agent; the dibutyltin dibutyrate, dibutyltin oxide and triester phosphate are catalysts and curing agents.

5. A method for preparing a high thermal conductivity and low viscosity silicone potting compound, characterized in that: The method is prepared according to the weight range of raw materials of the high thermal conductivity and low viscosity organic silicone potting adhesive according to claim 1, comprising the following preparation steps: Step 1, raw material preparation: weigh α, ω-dihydroxy polydiethylsiloxane, polyphenylsiloxane, spherical aluminum nitride, graphite powder, epoxy butyl oleate, organic bentonite, titanate coupling agent, dibutyltin dibutyrate, dibutyltin oxide and triester phosphate according to the formula weight; Step 2, pretreatment: surface modification of filler-graphite powder by chemical treatment method; Step 3, mixing: using a high shear mixer to mix α,ω-dihydroxy polydiethylsiloxane, polyphenylsiloxane, spherical aluminum nitride and graphite powder under set conditions to form a mixture; Step 4: Adding additives: lower the mixer temperature to 30-35°C, add epoxy butyl oleate, organic bentonite and titanate coupling agent to the mixture, and mix well; Step 5, vacuum degassing: vacuum degassing the mixture in the mixer; Step 6: Adding catalyst and curing agent: After lowering the temperature of the mixer and setting the mixing time, add dibutyltin dibutyrate, dibutyltin oxide and triester phosphate into the mixture and mix well; Step 7: Curing process: transfer the mixture to a potting container and set the required temperature and time for curing to form the final silicone potting glue; Step 8: Post-processing: The cured sealant is cut, polished and cleaned according to the manufacturer's needs; Step 9. Performance testing: Conduct performance tests on thermal conductivity, mechanical strength, flexibility and temperature resistance of the finished sealing glue.

6. The method for preparing a high thermal conductivity and low viscosity silicone potting adhesive according to claim 5, characterized in that: The filler-graphite powder in step 2 is subjected to modification treatment process: S1.1, pretreatment: put the graphite material into the oven, set the oven temperature to 90℃-110℃, and the oven drying time is 2-4h. When the moisture content of the material is detected to be lower than 0.1% by mass, stop the oven; S1.2, graphite powder: the dried material is powdered, the powdering time is set between 6-12 minutes, the powdering speed is set to 20000-25000r / min, and the graphite powder particles are controlled between 50-100 microns; S1.3, strong acid treatment method: immerse the graphite powder in 30% concentrated sulfuric acid and react at 80-95°C for 5-7 minutes to make the surface of the graphite particles hydrophilic.

7. The method for preparing a high thermal conductivity and low viscosity silicone potting adhesive according to claim 5, characterized in that: The mixing conditions in step 3 are: setting the temperature to 30-35° C., setting the stirring speed to 300-400 rpm, and setting the mixing time to 30-35 min.

8. The method for preparing a high thermal conductivity and low viscosity silicone potting adhesive according to claim 5, characterized in that: The vacuum degassing conditions in step 5 are as follows: the vacuum degree is set to 0.05-0.1 MPa, and the degassing time is between 10-15 minutes.

9. The method for preparing a high thermal conductivity and low viscosity silicone potting adhesive according to claim 5, characterized in that: The conditions for adding the catalyst and curing agent in step 6 are as follows: the mixer temperature is lowered to 20-25° C. and the mixing time is set to 20-30 min.

10. The method for preparing a high thermal conductivity and low viscosity silicone potting adhesive according to claim 5, characterized in that: The curing process in step seven is as follows: the mixture is transferred to a potting container, the temperature is controlled between 140-150° C., the time is controlled between 8-10 hours, the potting pressure is maintained between 2-3N, and a vacuum treatment is performed at the same time, and the mixture is cured under this condition to form a final silicone potting adhesive product.

Citation Information

Cited By

  • A high thermal conductivity, low viscosity, alcohol-free silicone rubber and its preparation method

    CN122542004A

  • Optical sensor package structure and electronic device

    US12388064B2

  • Optical sensor package structure and electronic device

    US20230246012A1